Analyses of the clinical and immunological characteristics of patients with lupus erythematosus - Min Deng; Ruifang Wu; Xingyu Zhou; Yuwen Su; Yaping Li (Wolters Kluwer Medknow Publications, 2022)
Background: Lupus erythematosus (LE) is a broad-spectrum, heterogeneous disease. At one end of the spectrum is the cutaneous LE (CLE) without systemic involvement, and at the other end is the systemic LE (SLE) with multisystem involvement. Analyses of clinical and immunological indicators and pathological examinations are helpful for early diagnosis, differential diagnosis, and prognosis of LE. Aim and Objectives: We described the clinical and laboratory characteristics of patients with LE and assessed the diagnostic value of immunohistochemical detection of C3d, C4d, IgG, IgG4, and CD123 in skin lesions of LE. Materials and Methods: Clinical and laboratory data of 62 patients with LE were collected. The expression levels of C3d, C4d, IgG, IgG4, and CD123 in skin lesions of LE were detected by immunohistochemistry (IHC). Results: Clinical manifestations such as hematological involvement, C3, C4, ESR, hematuresis, proteinuria, anti-Sm, anti-ribosomal P-protein, anti-U1-RNP, anti-histone, and anti-nucleosome antibodies are helpful for classificatory diagnosis of LE. The positive rate of C3d and/or C4d along the basement membrane zone in LE skin lesions by IHC was 74.6%, which was higher than that by direct immunofluorescence (47.5%) (P = 0.002). The expression of CD123 protein and the number of CD123+ plasmacytoid dendritic cells (PDCs) in skin lesions of patients with LE were higher than those of dermatomyositis (DM), while the distributed form of CD123 + PDCs in the dermis was different between LE and DM. Conclusions: The diagnosis of CLE and SLE requires a combination of clinical manifestations, laboratory indicators, and pathological examination. Immunohistochemical detection of C3d, C4d, and CD123 in skin lesions is important for the classificatory diagnosis of LE.